2010
DOI: 10.1590/s1413-70542010000300023
|View full text |Cite
|
Sign up to set email alerts
|

Sensibilidade do clorofilômetro para diagnóstico nutricional de nitrogênio no milho

Abstract: RESUMOA obtenção de altas produtividades de milho (Zea mays L.) torna-se difícil, dentre outros fatores, pela complexa quantificação dos requerimentos de nitrogênio (N) da cultura do milho ao longo do seu ciclo, o que dificulta o seu dimensionamento, ainda mais, considerando a variada capacidade de suprimento de N em solos brasileiros. Nesse sentido, os teores relativos de clorofila surgem como uma opção para o manejo do N. Objetivou-se, neste estudo avaliar a sensibilidade do clorofilômetro em indicar o estad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
3
9
1
5
Order By: Relevance
“…In this particular case, the organ in consideration is the leaf, being therefore incorporated into the membranes of the thylakoids as reaction centers called components of photo systems II and I (Taiz and Zeiger, 2013). Mean values of CRIL 03 V 5 (46.87) and CRIL 05 V 5 (55.69) were to be very close to that one obtained by Hurtado et al (2010) at V 4 to V 5 phenological stages, causing the maize crop to reach yields of 11.300 kg ha -1 found by such scientists, as well as by the current research (roughly corresponding to 11.684 kg ha -1 ). However, either CRIL 05 V 5 or mean yields were similar to the outcomes obtained by these authors.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…In this particular case, the organ in consideration is the leaf, being therefore incorporated into the membranes of the thylakoids as reaction centers called components of photo systems II and I (Taiz and Zeiger, 2013). Mean values of CRIL 03 V 5 (46.87) and CRIL 05 V 5 (55.69) were to be very close to that one obtained by Hurtado et al (2010) at V 4 to V 5 phenological stages, causing the maize crop to reach yields of 11.300 kg ha -1 found by such scientists, as well as by the current research (roughly corresponding to 11.684 kg ha -1 ). However, either CRIL 05 V 5 or mean yields were similar to the outcomes obtained by these authors.…”
Section: Resultssupporting
confidence: 86%
“…Average values obtained for the hybrids P30R50 and AG8025 was higher and similar to a CRI of 45.4% as cited by Argenta et al (2003) at the stage V 3 to V 4 , indicating that the content of N in the plant is quite adequate. The reading CRIL 03 V 4 did not correlate with the N content in the leaf, as well as with yield (Table 3), corroborating with Argenta et al (2002) and Hurtado et al (2010).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Amaral Filho et al (2005) also observed increases in leaf N content and in estimates of chlorophyll content and yield. Nevertheless, Hurtado et al (2010) evaluated the nutritional status of corn using a chlorophyll meter and found a need for up to 180 kg ha -1 N, exceeding the amount required to achieve maximum yield with 150 kg ha -1 (Souza et al, 2011).…”
Section: Resultsmentioning
confidence: 99%